2010
DOI: 10.2174/18749178010030200017
|View full text |Cite
|
Sign up to set email alerts
|

Getting into the Minds of Pairs of Liars and Truth Tellers: An Examination of Their Strategies

Abstract: Abstract:We examined the strategies used by 20 pairs of liars and 20 pairs of truth tellers when they were given the opportunity to prepare themselves for an interview in which they would be questioned about their whereabouts during a given period of time. More lying than truth telling pairs prepared themselves for the interviews. The truth tellers and liars who did prepare themselves used different verbal strategies but the same nonverbal strategies. Regarding verbal strategies, truth tellers were predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 13 publications
5
72
0
Order By: Relevance
“…Also, liars may feel that if they say too much, they may give their lies away (Vrij, 2008); that is why they indicated that they would tell an uncomplicated story with few details. This finding is consistent with previous research (Colwell et al, 2006;Vrij, Mann et al, 2010;but see Hartwig et al, 2007) as well as with theoretical considerations.…”
Section: General Strategies To Convince the Interviewersupporting
confidence: 94%
See 4 more Smart Citations
“…Also, liars may feel that if they say too much, they may give their lies away (Vrij, 2008); that is why they indicated that they would tell an uncomplicated story with few details. This finding is consistent with previous research (Colwell et al, 2006;Vrij, Mann et al, 2010;but see Hartwig et al, 2007) as well as with theoretical considerations.…”
Section: General Strategies To Convince the Interviewersupporting
confidence: 94%
“…Recently, deception scholars have turned their attention to the strategies that truth tellers and liars use to be convincing during an interview (Colwell, Hiscock-Anisman, Memon, Woods, & Michlik, 2006;Hartwig, Granhag, & Strömwall, 2007;Hartwig, Granhag, Strömwall, & Doering, 2010;Hines et al, 2010;Strömwall, Granhag, & Landström, 2007;Strömwall, Hartwig, & Granhag, 2006;Vrij, Mann, Leal, & Granhag, 2010). The reason for this is that knowledge about these strategies may be useful to anticipate the verbal and nonverbal behaviors of truth tellers and liars.…”
Section: Truth Tellers' and Liars' Strategiesmentioning
confidence: 99%
See 3 more Smart Citations